TELEVISI MEDIA APRESIASI SENI MASYARAKAT - Mardjono Mardjono (Institut Seni Indonesia Surakarta, 2013)
People’s appreciation in performing arts especially the traditional arts is still very low. Generally,people were more accustomed to popular arts which easily can be enjoyed daily on television,radio, and other mass medias. The youngsters are not appreciative of traditional performing artsthat are considering as ancient, not interesting, boring, etc. the technologies of mass medias suchas television have superiority as the media in communicating every art events to the societyhence the society can easily appreciate thus the sense of belonging will grow. In this context,television has strategic role as communication media in developing the society’s appreciation inarts. The symptom shows mass media’s, television’s particularly, role progress as an importantinstitution in society.